Jejak Kerajaan Islam Ende dan Sejarah Keagamaan di Flores - Muhamad Murtadho (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
The Kingdom of Ende marked the advent of Islam in Flores, East Nusa Tenggara. Portuguese power was limited to eastern part of Flores only such as Larantuka and Sikka. Meanwhile, Islam influenced western part of Flores.The rest area such like as Ngada was still dominated by animism. The development of Islam in Flores was dominated by political factor which means that Flores area was conquered by Islamic Kingdom of Sumbawa or Gowa Makassar. Other factors have also been determined by geographical factors such as natural condition of hills and only few population inhabiting the area. Consequently, the communication among Muslim at the time was very difficult. Islamic education were under developed. So, that is why Islam was not more well developed in that area than of any other area like Java, Sumatera, Sulawesi and other similar areas.This paper tries to enrich and make balance of publication or information deals with the history of Flores.